The influence of hydrogen on cyclic plasticity of <001> oriented nickel single crystal. Part II: Stability of edge dislocation dipoles. (June 2020) - Hachet, G.; Metsue, A.; Oudriss, A.; Feaugas, X.
Abstract: A competition between hardening and softening hydrogen effects on the cyclic behaviour of <001> oriented nickel single crystal has been observed and discussed in terms of effective and back stresses partitioning. Moreover, the consequences of hydrogen have been studied in terms of composite model which illustrates the interaction between hydrogen and dislocation organisation. The hydrogen hardening associated with dislocation wall phase is a key feature which has been discussed and elucidated at edge dislocation dipoles scale using atomic calculations in nickel single crystal. The aim of our study was to evaluate the stability of this dislocation organisation in the presence of hydrogen, vacancies and vacancy clusters. As the main result, we noted that hydrogen in Cottrell's atmosphere hardens dipole configurations following solid solution strengthening and vacancies induced by hydrogen incorporation and cyclic loading attenuate this result. Moreover, the consequences of vacancies are more important when they are regrouped as clusters than when they are homogeneously distributed in the Cottrell's atmosphere. Such results can explain the complex behaviour of the wall phase and the consequence on long-range internal stresses observed in the first part of this study. Highlights: The stability of dislocation dipoles was evaluated with the critical stress breaking their elastic equilibrium. The stress was calculated in presence of hydrogen, vacancies and vacancies clusters with numerical and analytical approaches. Hydrogen increased the critical stress, inducing a hardening of dislocation dipoles, which follows a MNL model. Vacancies attenuated this hardening, also the attenuation was even more important when they are regrouped as clusters. These results from MD and calorimetry can explain the complex behaviour of the back stress noted the first part of this study.